PENGARUH TENURE KAP DAN AUDIT FEE TERHADAP KUALITAS AUDIT DENGAN DIMODERASI KOMITE AUDIT - Tia Apriani; Megawati (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Ilmu Ekonomi (STIE) Pontianak, 2021)
This study aims to examine and analyze the influence of KAP tenure and audit fees on audit quality by moderating the audit committee. This type of research is quantitative research, using secondary data in the form of data from annual reports and financial reportscompanies listed on the Indonesia Stock Exchange. The population selected in the study as the object of research are manufacturing companies listed on the Indonesia Stock Exchange (IDX) in the year 2015-2017. The analytical method in this study is Moderated Regression Analysis (MRA) and SPSS version 24 statistical analysis. The results show that KAP tenure and audit fees have no effect on audit quality. The audit committee moderation variable is not able to moderate the relationship between KAP tenure and audit fee on audit quality.